Correlation between transport properties of a-Si:H layers and cell performances incorporating these layers - Wyrsch, Nicolas; Beck, N.; Hof, Ch.; Goerlitzer, M.; Shah, Arvind (My University, 1996)
Using the new ‘quality parameter’, μ0τ0, the authors were able to show, for the first time, a clear correlation between transport properties of a series of a-Si:H films (grown at various deposition temperatures) and the efficiency of p-i-n cells incorporating the same material as i-layer. In this paper, additional experimental data are presented sustaining, on one hand, the validity of the proposed ‘quality parameter’, μoτo, and on the other hand, the existence of a correlation between cell performances and transport properties. Furthermore, limitations of this correlation, due to technological problems (e.g., chemical contamination by Na, O,…) involved in the practical fabrication of a-Si:H solar cells are also illustrated and discussed.